The Military Vocabulary as a Component of Achilles Tatius’s Idiostyle - Inesa Chakal (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The article attempts to characterize military vocabulary as an integral component of Achilles Tatius’s idiostyle, of an ancient Greek writer of the 2nd century AD, the author of one of the first love novels that have survived to our days in full – "Leucippe and Clitophon".